Improvement in the size and antioxidant activity of kafirin microparticles by treatment with sorghum polyphenols - Taylor, J.R.N. (John Reginald Nuttall) (University of Pretoria, 2014)
Dissertation (MSc)--University of Pretoria, 2013.